Alzheimer's Disease and the Elderly in Israel: Are We Paying Enough Attention to the Topic in the Arab Population?. (August 2015) - Werner, Perla; Friedland, Robert P.; Inzelberg, Rivka
With the continuing rise in the elderly population, Alzheimer's disease (AD) and dementia represent an increasing public health concern worldwide. In recent years, research has focused on the relationship between AD and ethnicity. Israel, a multiethnic society, provides a natural laboratory for research on ethnicity and health. The largest ethnic group is that of Israeli Jews, followed by Arab citizens, mostly Arab Muslims, with smaller numbers of Arab Christians in addition to Druze, Circassians, and others. The aim of this review is to clarify ethnic differences in prevalence and risk factors for Alzheimer's disease. We review available literature on ethnic differences in epidemiologic and risk factors for Alzheimer's disease, including genetic differences as well as disparities in health access and quality of health services. We will conclude with research and policy implications.